Investigating cross-clade immune responses in HIV-1 subtype C-infected individuals from South Africa: implications for HIV vaccine design - Zembe, Lycias (Division of Virology, 2016)
Background An effective HIV vaccine remains the main hope for controlling the HIV epidemic and is a global health priority. The genetic diversity of the virus across the globe is a major impediment to developing an effective vaccine. Whether a universal vaccine is possible still remain elusive. Therefore, there is need to fully characterise clusters of commonly targeted regions across the different HIV-1 clades. Centralized sequences have been suggested as vaccine immunogens and peptide reagents for assessing vaccine-induced responses, but their cross-reactivity has not been fully assessed in larger cohorts of subtype C-infection and in regions of differing HIV epidemics. In addition, the functional profile of HIV-specific T-cells recognizing variant epitopes has not been fully characterized. Whether cross-reactivity observed by IFN-γ production in an ELISpot assay can be observed at physiological concentrations of the peptides and for other functions of HIV-specific T-cells is an important question that remains to be answered. Methods The cross-reactivity of HIV-specific T-cells was assessed using clade-specific peptide reagents forming part of current candidate vaccine inserts based on the HIV-1 Gag protein from clades CDu422, CCH, A, B and D in 40 clade C-infected study participants using the IFN-γ ELISpot assay. To test the reactivity of group M consensus peptide reagents, 66 individuals, 44 of whom were ARV naïve, were assessed for HIV-specific T cell responses to group M Gag and Nef peptides. A selection of these individuals was screened for HIVspecific T-cell responses to clade CDu422 Gag peptides. Cross-reactivity of peptide variants was assessed at physiologically relevant peptide concentrations by functional avidity studies using peptide dilution IFN-γ ELISpot assays. Additionally, the cytokine profile, cytotoxic potential and proliferative capacity of cross-reactive peptide variants was characterised using multiparameter flow cytometry. Results The magnitude and breadth of HIV-specific T-cell responses were similar between the two clade-C peptide reagents in a clade C-infected population. However, the magnitude and breadth of responses to peptides based on clades A, B and D were significantly lower compared to the clade C peptides. Clusters of commonly targeted regions cross-reactive across the four clades investigated resided predominantly in conserved regions. Interestingly, there were Gag regions that were exclusively recognized in the different clades that had significantly lower entropy scores for the reactive variants than their nonreactive counterparts, suggesting that the variability in targeted regions could have been shaped by host immune pressure. For consensus group M peptides, the magnitude and breadth of Gag responses were significantly higher than that of Nef in clade C-infected individuals. In addition, consensus group M Gag peptides had significantly lower magnitude and breadth of HIV-specific T-cell responses compared to clade C peptide reagents, suggesting loss of responses by centralised reagents despite their central nature to group M viruses. On the contrary, the magnitude and breadth of responses to consensus group M Gag peptides were comparable to that of clade-mismatched peptides, namely clades A, B and D, suggesting that these reagents can be used interchangeably. Peptide dilution assays showed that amino acid mismatches have discordant effects on functional avidity and that some peptides are cross-reactive at physiological concentrations. Similarly, discordant effects (differences in functional avidity, cytokine and cytotoxic profiles and proliferative capacity) of amino acid mismatches on cytokine and cytotoxic potential profiles as well as proliferative capacity were observed. Conclusion People infected by a particular HIV clade can recognize HIV peptides based on other clades. However, the magnitude and breadth of responses are greater for the matched clades compared to mismatched clades, suggesting that there may be an advantage of using vaccines based on matched over unmatched clades. Group M based consensus sequences can be recognized in HIV-infected individuals, but with a lower frequency, magnitude and breadth of responses compared to clade-matched peptides, suggesting a limitation of these peptides both as reagents and vaccine immunogens. However, the frequency, magnitude and breadth T-cell reponses to consensus group M peptides were comparable to clademismatched responses, suggesting that these reagents may be used interchangeably. Furthermore, amino acid variations across corresponding viral regions have discordant effects on the functional avidity, cytokine profile, cytotoxic potential and proliferative capacity; implying that qualitative measures of cross-reactivity beyond IFN-γ frequencies need to be considered. These data may aid in the development of reagents for the assessment of vaccine-induced responses as well as in HIV vaccine immunogen design.